2019
DOI: 10.3389/fchem.2019.00756
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica vs. Organosilica Composites to Desulfurize Diesel

Abstract: The monolacunary Keggin-type [PW11O39]7− (PW11) heteropolyanion was immobilized on porous framework of mesoporous silicas, namely SBA-15 and an ethylene-bridged periodic mesoporous organosilica (PMOE). The supports were functionalized with a cationic group (N-trimethoxysilypropyl-N, N, N-trimethylammonium, TMA) for the successful anchoring of the anionic polyoxometalate. The PW11@TMA-SBA-15 and PW11@TMA-PMOE composites were evaluated as heterogeneous catalysts in the oxidative desulfurization of a model diesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Oxidative desulfurization studies on amine functionalized SBA-15 supports revealed high performance in case of PW 11 @aptesSBA-15, which could completely desulfurize simulated diesel in solvent-free conditions with half the oxidant amount (H 2 O 2 /S = 4), whereas it showed 83.4% efficiency in case of real unthread diesel (in a biphasic system, 1:1 diesel/acetonitrile) with a recycle capacity for eight consecutive cycles. Their recent work involved impregnation of PW 11 on cationic group ( N -trimethoxysilypropyl- N, N, N -trimethylammonium, TMA) functionalized MS supports [ 101 ]. Here, two kinds of MS supports were selected (ordered MS, SBA-15, and an ethylene-bridged periodic mesoporous organosilica, PMOE) and two catalysts were prepared, PW 11 @TMA-SBA-15 and PW 11 @TMA-PMOE.…”
Section: Mesoporous Silica and Mesoporous Silica Nanoparticles In mentioning
confidence: 99%
See 4 more Smart Citations
“…Oxidative desulfurization studies on amine functionalized SBA-15 supports revealed high performance in case of PW 11 @aptesSBA-15, which could completely desulfurize simulated diesel in solvent-free conditions with half the oxidant amount (H 2 O 2 /S = 4), whereas it showed 83.4% efficiency in case of real unthread diesel (in a biphasic system, 1:1 diesel/acetonitrile) with a recycle capacity for eight consecutive cycles. Their recent work involved impregnation of PW 11 on cationic group ( N -trimethoxysilypropyl- N, N, N -trimethylammonium, TMA) functionalized MS supports [ 101 ]. Here, two kinds of MS supports were selected (ordered MS, SBA-15, and an ethylene-bridged periodic mesoporous organosilica, PMOE) and two catalysts were prepared, PW 11 @TMA-SBA-15 and PW 11 @TMA-PMOE.…”
Section: Mesoporous Silica and Mesoporous Silica Nanoparticles In mentioning
confidence: 99%
“…A remarkable desulfurization performance was exhibited by the PW 11 @TMA-SBA-15 catalyst, which could achieve ultra-low sulfur levels (<10 ppm) in both biphasic, as well as solvent-free conditions, and could be recycled six consecutive times without appreciable loss of catalytic activity. This promising catalyst was also tested on untreated real diesel provided by Spanish petroleum company, CEPSA (1335 ppm S) under biphasic system and demonstrated 90% desulfurization efficiency for 3 consecutive cycles [ 101 ].…”
Section: Mesoporous Silica and Mesoporous Silica Nanoparticles In mentioning
confidence: 99%
See 3 more Smart Citations